ANALISIS TINGKAT KEPUASAN MAHASISWATERHADAP SARANA DAN PRASARANA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Lestari, Nila Suci; Suarman, Suarman; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the quality of facilities and infrastructure of the Economic Education Study Program FKIP University of Riau and to determine the level of student satisfaction with the facilities and infrastructure of the Economic Education Study Program FKIP Riau University. The population in this study was the population in this study were students of Economic Education Study Program Faculty of Teacher Training and Education, University of Riau force 2016 and 2017 which amounted to 153 people and the sample in this study amounted to 60 respondents. The technique of collecting data uses a questionnaire. The data analysis method used is the analysis of Importance Performance Analysis (IPA). From the IPA results it can be seen that the attributes of factors that influence student satisfaction. In quadrant A (top priority) there are 8 attributes, and in quadrant B (good position) there are 6 attributes, and in quadrant C (low priority) there are also 6 attributes, while in quadrant D (excessive position) there are 5 attributes. From the table of conformity level, it can be seen that the lowest level of suitability of all dimensions is a comfortable and clean toilet attribute when used that is equal to 56.59%, while the highest average level of suitability is the attribute of classrooms availability according to class schedule which is 80.76%. Of the 25 attributes in general the average of the attribute suitability level has not reached 100%, but the respondents considered that the level of service quality of facilities and infrastructure of the Economic Study Program was quite good because the value of student satisfaction reached 69.58%. Judging from the level of gap or gap, it can be concluded that there is no match between expectations and reality experienced by the Economics Education Study Program students. Because of the 25 attributes there are 16 attributes included in the category of inequality that are not good, among others: attribute classrooms are free from noise during learning, attribute the amount of air conditioning or an adequate fan in the classroom, attribute AC or fan angina that lights up with both when the learning process takes place in the classroom, attributes the availability of learning media for lecture purposes, attributes there are infocus that can be used in the learning process, slide attributes or images generated by the focus can be clearly seen by students.Key Words: Service Quality, Satisfaction, Facilities and Infastructure